Alternative Care for Children in Botswana: a Reality or Idealism? - Tumani Malinga; Poloko N. Ntshwarang (Social Work and Society)
The world is experiencing an increase in the numbers of children requiring care, and Botswana is no exception. There are various alternative methods used to aid vulnerable children (VC).Â  Formal alternative care giving arrangements for children in need of care include residential care, formal adoption and guardianship sanctioned by the courts. Historically, kinship care was used to address the needs of vulnerable children. However, African societies, including Botswana are going through a process of rapid social, economic, and cultural change and families are living under extreme poverty, and finding it difficult to extend help to other relatives. Even though some alternative methods are available, there is need for them to be revisited to examine whether the best interests of the child are met. This article explores the alternative care methods for children in Botswana. It looks at the method's strengths and challenges. Supporting vulnerable children is critical to the future of sub-Saharan Africa and urgent action is essential. The paper discusses the implications of the methods of alternative care and calls for community, national, and international responses.Â  It also argues for the need for technical and financial resources to critically address the escalating needs of the country's vulnerable children.Â